Cow Milk Total Protein Analysis and Daily Intake Estimation in Armenia - Hovhannisyan, A. S.; Beglaryan, M. R.; Pipoyan, D. A.; Merendino, N. (ՀԱԱՀ հիմնադրամ)
Protein plays a critical role in both the nutrition and biological functions of milk, which is an important part of a balanced diet. In this study, we installed and implemented the fully automated Kjeldahl method, enabling the precise determination of the total protein content in cow milk. The investigation involved cow milk samples collected from Yerevan markets, representing 9 producers, over the years 2021 and 2022. The mean total protein content in the analyzed milk samples was found to be 2.93 g per 100 g.To determine the significance and contribution of milk protein in the adult population’s diet in Armenia, the daily protein intake through milk consumption was evaluated. Two consumer clusters were identified: one with moderate milk consumption (0.067 kg per day) and another with higher intake (0.208 kg per day). The contribution of milk protein to the overall protein intake in the diet of the adult population ranged from 2.62 % to 8.13 %. Despite varied levels of milk protein consumption, it is essential to acknowledge that Armenian protein sources extend beyond milk.
Keywords: Food Science and Technology